2006
DOI: 10.3797/scipharm.2006.74.121
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Flow Injection Analysis of Bromhexine Hydrochloride and its Pharmaceutical Preparation Using Conventional and Coated Wire Ion-Selective Electrodes

Abstract: Bromhexine hydrochloridei on-selectivee lectrodes (conventionalt ype)b ased on bromhexinium tetraphenylb orate( I) andb romhexinium-phosphotungstate (II) were prepared.T he electrodes exhibitedm ean slopes of calibration graphs of 59.4 mV and 59.8 mV per decade of bromhexine concentrationa t2 5 Cf or electrode (I) and (II),r espectively.B oth electrodes couldb eu sed within the concentrationr ange 3.16x10-5 -1.00x10 -2 Mb romhexine within the pH range 2.0-4.5. The standard electrodes potentials were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, BH-HCl is one of the mucous-modifying drugs that aid expectoration by improving the flow characteristics of bronchial mucous [3,4]. A literature review indicated the determination of bromhexine hydrochloride in dosage form, either in combined form or alone, by spectrophotometric [5][6][7][8][9][10][11], potentiometric [12], voltammetric [13], colorimetric [14], chemiluminescence [15,16], TLC [17], HPLC [18][19][20][21][22][23][24][25], RRLC-MS/MS [26], and HPTLC-HPLC [27]. This study presents a new method to determine BH-HCl in pharmaceutical formulations using tetraphenylborate as a precipitating reagent to form a yellowish-white precipitate with the use of a homemade instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BH-HCl is one of the mucous-modifying drugs that aid expectoration by improving the flow characteristics of bronchial mucous [3,4]. A literature review indicated the determination of bromhexine hydrochloride in dosage form, either in combined form or alone, by spectrophotometric [5][6][7][8][9][10][11], potentiometric [12], voltammetric [13], colorimetric [14], chemiluminescence [15,16], TLC [17], HPLC [18][19][20][21][22][23][24][25], RRLC-MS/MS [26], and HPTLC-HPLC [27]. This study presents a new method to determine BH-HCl in pharmaceutical formulations using tetraphenylborate as a precipitating reagent to form a yellowish-white precipitate with the use of a homemade instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Assisting vasomotor secretion generates a vasomotor secretory effect [5]. Several analytical techniques were used to estimate bromohexine HCl in medicinal formulations such as Potentiometric Flow Injection [6], HPLC-ICP-MS [7], HPLC [8], Thin Layer Chromatography (TLC) [9], Spectrophotometric Quantitative [10], and UV-Vis Spectrophotometer [11][12] [13]. The dispersive liquid liquid microextraction (DLLME) and cloud point extraction have many advantages in the determination of pharmaceutical preparation like rapid, safety and low cost [14].In this work, the proposed technique is based ion-pair reaction of bromohexine HCl with alizarin yellow reagent in the acidic medium, then evaluation and pre-concentration…”
Section: Introductionmentioning
confidence: 99%
“…Because of its physiological importance, the drug has been quantified by exploiting its chemical 5,6 and physical properties [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . The different analytical methods used to quantify the drug as a single active pharmaceutical ingredient include flow injection analysis with ion RESEARCH ARTICLE selective electrodes 7 , inductively coupled plasma mass spectrometry 8 , electrokinetic chromatography 9 , electrochemical oxidation at the glassy carbon electrode 10 , liquidchromatography 11 , liquid gas chromatography 12 , GC with mass detection 13 and voltammetry 14 .…”
Section: Introductionmentioning
confidence: 99%